MENGANALISIS KINERJA KEUANGAN: PENDEKATAN PERSAMAAN SIMULTAN PADA SEPULUH BANK SYARIAH TERBESAR INDONESIA - Zahra, Surti; Komarudin, Mamay; Tabroni, Tabroni (Gapenas Publisher, 2025)
Objective: This study aims to explore how various factors simultaneously affect financial outcomes in the ten largest Islamic banking institutions in Indonesia through a recursive block simultaneous equation model. The main focus is on addressing the issue of endogeny inherent in performance measurement systems. Design/methodology/approach: Using quarterly panel data for the period 2020 to 2024 from the ten largest Islamic banks in Indonesia, this study applies the Three Stage Least Squares estimation technique to analyze three interrelated subsystems, namely profit performance measured through ROA, cost management effectiveness captured by BOPO, and portfolio quality demonstrated by NPF. The simultaneous framework used is able to reveal the reciprocal relationships and feedback mechanisms that operate between the endogenous constructs. Findings: The results of empirical estimation show a significant simultaneous relationship between various performance dimensions. Cost inefficiencies were shown to significantly reduce profitability (?? = negative 0.0847, p less than 0.01), while a decrease in portfolio quality had a negative impact on revenue (?? = negative 0.2341, p less than 0.01). The reciprocal influence showed that increased profitability drove cost efficiency (?? = negative 0.3156, p less than 0.01) and strengthened portfolio quality (?? = negative 0.1823, p less than 0.05). The scale of the institution and the strength of capital play a crucial role as drivers of performance, while macroeconomic factors show varying impacts across the various analysis blocks. Limitations/implications of the study: This study focused on only ten leading institutions, so the possibilities are limited to generalizing to smaller market participants. Further research may incorporate nonlinear specifications and broader risk measurement frameworks. Practical implications: Empirical evidence suggests that Islamic banking institutions need to prioritize improving cost efficiencies to build a sustainable revenue trajectory. Supervisory authorities need to understand the interrelated performance dynamics when designing prudential supervision mechanisms for Islamic financial institutions. Originality/value: This study contributes to the Islamic banking literature by applying simultaneous equation techniques to capture complex interdependencies that have rarely been studied before, resulting in a comprehensive perspective on the operational dynamics of Indonesian Islamic banking.